Implementasi Fikih Muamalah dalam Ekonomi Kreatif Membangun Mahasiswa Muslim Entrepreneur - Asep Supriatna; Moch. Hoerul Gunawan; Dicky Maulidhany; Dindin Dimyati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Muamalah jurisprudence is an important part of sharia economics which regulates various aspects of business transactions so that they are in accordance with Islamic principles. The implementation of muamalah fiqh in creative entrepreneurship among students is very relevant, considering the importance of building an entrepreneurial character that is not only economically profitable, but also in accordance with sharia. This research aims to analyze the application of muamalah fiqh in creative entrepreneurial activities among STIT Rakeyan Santang students and identify the obstacles faced in its implementation. The research method used is descriptive quantitative with a survey approach. Data was collected through questionnaires distributed to students involved in entrepreneurship, as well as interviews to explore opinions in more depth. The research results show that although the majority of students have a basic understanding of the principles of muamalah fiqh, they experience difficulties in applying them in creative business. Around 70% of students stated the need for practical training related to the application of muamalah fiqh in their business. The implication of this research is the importance of developing a curriculum that is more practice-based and applying muamalah fiqh in the business world, as well as providing relevant training to improve students' entrepreneurial skills in accordance with sharia principles.